2013
DOI: 10.5455/msm.2013.25.242-245
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Change in Air Humidity and the Incidence of Stroke

Abstract: Introduction:According to the World Health Organization estimates annually in the world die due to CVI every sixth women and 10th man. This paper is the research of the correlation between changes in relative air humidity and stroke (CVA) in the Sarajevo Canton. Included are patients who experienced an acute stroke in the Canton of Sarajevo and treated in the pre hospital phase by the staff of the Institute for Emergency Medicine. Days with stroke and those without cases of stroke were compared within three ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…A 3-year retrospective study in Sarajevo reported that extreme levels of humidity were significantly associated with the incidence of stroke [17]. Another study -in Boston -showed an association between stroke and cooler temperatures, especially on days with higher levels of relative humidity [5].…”
Section: An Association Between Atmospheric Pollution and Stroke Mortality In England Andmentioning
confidence: 99%
“…A 3-year retrospective study in Sarajevo reported that extreme levels of humidity were significantly associated with the incidence of stroke [17]. Another study -in Boston -showed an association between stroke and cooler temperatures, especially on days with higher levels of relative humidity [5].…”
Section: An Association Between Atmospheric Pollution and Stroke Mortality In England Andmentioning
confidence: 99%
“…However, a systematic review showed no association between daily humidity and cerebrovascular disease occurrence [14]. A previous study revealed that extremely low or high humidity correlated with the incidence of stroke [15]. High humidity can cause dehydration, which increases the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Summers are cool and winters are long and hard in Ardahan (8). Slatina et al (22) showed that seasonal changes had no effect on stroke frequency. However, in two studies from Turkey, ischemic stroke was more frequent in the summer months (6,23).…”
Section: Discussionmentioning
confidence: 99%